(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
This paper provides answer to the following question. Does the performance of students depend on the location of accommodation and facilities? The Chi square and the likelihood ratio Chi square statistics based on the contingency table are applied to answer the above question. The statistical analysis using the above techniques revealed that students performance depends on the location of the accommodation and the facilities. Result based on the odd ratio indicated that there is no association between accommodation location and facilities.